2007
DOI: 10.1002/acp.1356
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about the meaning and measurement of intelligence: a cross‐cultural comparison of American, British and Malaysian undergraduates

Abstract: This study examined lay beliefs about intelligence cross-culturally using a questionnaire based on an expert summary of what is known about intelligence. Two hundred and thirty five university undergraduates in Malaysia, 347 undergraduates in Britain and 137 undergraduates in the US rated for agreement 30 items about the nature, measurement, between-group differences and practical importance of intelligence. An exploratory factor analysis revealed three factors: (1) stability, reliability and validity of intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…First, the intelligence items chosen from Sternberg (emotional, creative and practical intelligence) are not the ones that Sternberg has shown to correspond with lay beliefs about intelligence (see Sternberg & Berg, 1992), namely verbal competence, everyday competence and interest in, and ability to deal with, novelty. Moreover, a number of recent studies have suggested that there may be important differences in the way intelligence is defined and understood across cultures (e.g., Grigorenko et al, 2001; Sternberg & Grigorenko, 2006; Swami et al, 2008). Future studies may therefore choose to use intelligence items that are more directly derived from lay understandings of intelligence or cross‐cultural research.…”
Section: Discussionmentioning
confidence: 99%
“…First, the intelligence items chosen from Sternberg (emotional, creative and practical intelligence) are not the ones that Sternberg has shown to correspond with lay beliefs about intelligence (see Sternberg & Berg, 1992), namely verbal competence, everyday competence and interest in, and ability to deal with, novelty. Moreover, a number of recent studies have suggested that there may be important differences in the way intelligence is defined and understood across cultures (e.g., Grigorenko et al, 2001; Sternberg & Grigorenko, 2006; Swami et al, 2008). Future studies may therefore choose to use intelligence items that are more directly derived from lay understandings of intelligence or cross‐cultural research.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Swami and colleagues compared levels of agreement about three domains of findings of intelligence research-(1) Stability, validity, and reliability of intelligence tests, (2) Practical importance of intelligence, and (3) Source and stability of within-group differences-in three countries: the U.S., Britain, and Malaysia. The authors determined that the British and American samples were more skeptical about findings related to the first two domains; that is, they were less likely to believe that intelligence tests were good measures of intelligence and that intelligence has practical importance [27]. If we extend this finding to the SAT as a measure of cognitive ability, the public perception becomes intelligence isn't measured by the SAT and SAT scores don't matter.…”
Section: Why the Resistance To Sat Intelligence And Achievement Relmentioning
confidence: 99%
“…Lay views of intelligence frequently acknowledge the role of genetics and early environment, but differ on the importance intelligence plays in everyday life (e.g., Dweck, Chiu, & Hong, 1995;Flugel, 1947;Plous & Williams, 1995;Swami et al, 2008). Dweck et al (1995) noted, for example, that people differ in their belief that intelligence is fixed versus whether it can be changed and developed.…”
Section: Hypothesesmentioning
confidence: 99%
“…Dweck et al () noted, for example, that people differ in their belief that intelligence is fixed versus whether it can be changed and developed. Swami et al () found considerable variance, both within and across countries, in the degree to which people believed that intelligence predicts important educational, occupational, and economic outcomes. Scientific determinism reflects the belief that behavior is influenced by biological and environmental forces (Carey & Paulhus, ).…”
Section: Free Will and Determinismmentioning
confidence: 99%